2021
DOI: 10.3390/vaccines9070783
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Health Behavior Theories to Predict COVID-19 Vaccine Acceptance: Differences between Medical Students and Nursing Students

Abstract: Background: This study aimed to explore behavioral-related factors predicting the intention of getting a COVID-19 vaccine among medical and nursing students using an integrative model combining the Health Belief Model (HBM) and the Theory of Planned Behavior (TPB). Methods: A cross-sectional online survey was conducted among medical and nursing students aged > 18 years in their clinical years in Israel between 27 August and 28 September 2020. Hierarchical logistic regression was used to predict acceptance o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 32 publications
(66 reference statements)
3
40
0
1
Order By: Relevance
“…The availability of vaccination, or the percentage of vaccinated students might be associated with vaccination hesitancy. Several studies have shown that medical students express higher intentions to be vaccinated than the general population [24], nonmedical students [25,26], nursing students [27], and dental students [28]. A recent study conducted in Japan showed that 14 to 16% of the younger (15-39 years old) subgroup expressed COVID-19 vaccine hesitancy in terms of their hypothetical intention to be vaccinated and that vaccination intention was associated with several factors, including younger age, female sex, and living alone [29].…”
Section: Discussionmentioning
confidence: 99%
“…The availability of vaccination, or the percentage of vaccinated students might be associated with vaccination hesitancy. Several studies have shown that medical students express higher intentions to be vaccinated than the general population [24], nonmedical students [25,26], nursing students [27], and dental students [28]. A recent study conducted in Japan showed that 14 to 16% of the younger (15-39 years old) subgroup expressed COVID-19 vaccine hesitancy in terms of their hypothetical intention to be vaccinated and that vaccination intention was associated with several factors, including younger age, female sex, and living alone [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, lower coverages were also found in other studies conducted in Slovakia and Japan among medical students where the coverages were 71.7% [33] and 89.1% [34], respectively. Perhaps the differences are due to greater reliance on the vaccine over time, the educational environment or differences in the type of vaccine available in each country [35][36][37].…”
Section: Vaccination Coverage Against Sars-cov-2mentioning
confidence: 99%
“…Other sources were television, newspapers, politicians, family, radio, and religious or cultural leaders [14]. A study from Israel among medical and nursing students found higher motivation for vaccination in students that were recommended to get vaccinate by their family, friends, colleagues, or supervisors [41].…”
Section: The Effect Of Fear Of Covid-19 On Vaccination Attitudesmentioning
confidence: 99%